Hitler's bureaucrats : the Nazi security police and the banality of evil - Lozowick, Yaakov 1957- (Continuum, 2002)
From theory to practice : 1933-8 -- Documents in the bureaucratic system -- Toward the final solution -- Executing the final solution in Germany -- Holland -- France -- Hungary